2017
DOI: 10.1002/rcm.7814
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of crude oil asphaltenes by coupling size‐exclusion chromatography directly to an ultrahigh‐resolution mass spectrometer

Abstract: Direct coupling of SEC with ultrahigh-resolution mass spectrometry allows the study of the most difficult to analyze fraction of crude oil, the asphaltene fraction. Separation reduces the complexity of individual spectra and, therefore, also reduces suppression and discrimination effects. The separation of structural isomers which cannot be characterized by MS alone gives an added dimension to the analysis of asphaltenes. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Ultra-high-resolution analyses on the Orbitrap Elite instrument were performed in a targeted selected ion monitoring (t-SIM) mode. The mass resolution R m / z 200 = 1.35 × 10 6 was reached by acquiring 3 s transients and processing them in enhanced Fourier transform (eFT) mode under AGC values of 3 × 10 3 , 1.5 × 10 4 , and 5 × 10 4 and maximum fill time of 500 ms. Extended (3 s vs default 1.5 s) transient acquisition time was enabled by developer’s kit functionality using Instrument Control Language (ICL). , If required, it could be further extended up to 6 s, reaching R m / z 650 = 1.2 × 10 6 (Figure S1). The S-lens radio frequency level and capillary temperature were as above.…”
Section: Methodsmentioning
confidence: 99%
“…Ultra-high-resolution analyses on the Orbitrap Elite instrument were performed in a targeted selected ion monitoring (t-SIM) mode. The mass resolution R m / z 200 = 1.35 × 10 6 was reached by acquiring 3 s transients and processing them in enhanced Fourier transform (eFT) mode under AGC values of 3 × 10 3 , 1.5 × 10 4 , and 5 × 10 4 and maximum fill time of 500 ms. Extended (3 s vs default 1.5 s) transient acquisition time was enabled by developer’s kit functionality using Instrument Control Language (ICL). , If required, it could be further extended up to 6 s, reaching R m / z 650 = 1.2 × 10 6 (Figure S1). The S-lens radio frequency level and capillary temperature were as above.…”
Section: Methodsmentioning
confidence: 99%
“…UV-fluorescence was not sensitive for high-mass fractions and could not detect asphaltene with MW higher than 30 0 0 Da. As mentioned above, only MS could accurately achieve MW of low-and high-MW fractions for size-separated fractions [137] .…”
Section: High Performance Liquid Chromatography (Hplc)mentioning
confidence: 97%
“…Over the past decade, advances in both ionization techniques and high-resolution mass spectrometers have led to the coupling of chromatography and high-resolution mass spectrometry for the analysis of ultracomplex samples. Schrader et al have published a series of works that utilize online liquid chromatography–mass spectrometry (LC-MS) to study both crude oils and asphaltenes. Robson and co-workers showed good separation of nitrogen compounds after off-line fractionation, thereby showing the need for the combined resolution of online LC-MS for a complex mixture analysis . More recently, Gavard et al reported a software suite, Kairos MS, for processing of hyphenated ultra-high-resolution mass spectrometry data.…”
Section: Introductionmentioning
confidence: 99%